Kajian Kesesuaian dan Daya Dukung Wilayah Pesisir Pantai Bandengan Jepara, sebagai Upaya Optimalisasi Pengembangan Kegiatan Wisata Bahari - Budhiawan, Gigih; Indarjo, Agus; Suryono, Suryono (977-2407769)
Bandengan Beach is quite famous and become mainstay Jepara Regency until be destination is quite popular, not only for Jepara people but also majority Central Java People. Nowadays, tourism activities in Bandengan Beach very limited recreation, enjoy to the landscape beach, and swimming. While still many potential area not yet be used maximum. This Study intend to assign suitable location for development marine tourism activity, know extents area development and capacity unit area that intended of tourism activity water sports. The Research results represent that tourism activities in Bandengan Beach Jepara Regency potential to be developed tourism especially water sports. Suitable location is 200 m from the shoreline towards middle sea at depth of > 5 meters. This area has a category S1 (very suitable) with values IKW 87.50 %. Tourism activities that can be developed among others, Flying Fish and Rolling Donuts in addition to existing tourist activities in advance Jet Ski and Banana Boat. The area that can be used is 74.000 m2 around 7.4 hectares and has a capacity of maximum expected around 148 person Jetski and 148 person Banana Boat tourist effective daily.